Brain serotonin 2A receptor binding predicts subjective temporal and mystical effects of psilocybin in healthy humans - Stenbæk, Dea Siggaard; Madsen, Martin Korsbak; Ozenne, Brice; Kristiansen, Sara; Burmester, Daniel; Erritzoe, David; Knudsen, Gitte Moos; Fisher, Patrick MacDonald (Journal of psychopharmacology (Oxford), 2021)
Psilocybin is a serotonergic psychedelic with psychoactive effects mediated by serotonin 2A receptor (5-HT2AR) activation. It produces an acute psychedelic altered state of consciousness with a unique phenomenology that can be temporally characterized by three intensity phases: onset of psychoactive effect, a peak plateau and return to normal consciousness. We evaluated whether pre-drug brain 5-HT2AR binding predicted the three phases of psilocybin subjective drug intensity (SDI) and retrospective self-report of mystical type experiences in healthy individuals. Sixteen participants completed a pre-drug [ C]Cimbi-36 positron emission tomography scan to assess 5-HT2AR binding. On a separate day, participants completed a single psilocybin session (oral dose range 0.2-0.3 mg/kg), during which SDI was assessed every 20 min. The Mystical Experience Questionnaire (MEQ) was completed at the end of the session. The three SDI phases were modelled using segmented linear regressions. We evaluated the associations between neocortex 5-HT2AR binding and SDI/MEQ outcomes using linear regression models. Neocortex 5-HT2AR was statistically significantly negatively associated with peak plateau duration and positively with time to return to normal waking consciousness. It was also statistically significantly negatively associated with MEQ total score. This is the first study to investigate how individual brain 5-HT2AR binding predicts subjective effects of a single dose of psilocybin. Our findings reinforce the role of cerebral 5-HT2AR in shaping the temporal and mystical features of the psychedelic experience. Future studies should examine whether individual brain levels of 5-HT2AR have an impact on therapeutic outcomes in clinical studies.